Transmissibility and other characteristics of HPAI in Indonesian village poultry - Jost, Christine; Bett, Bernard K.; Poole, Elizabeth J.; Azar, M.; Murahman, J.; Daju, D.; McLaws, M.; Schoonman, L.; Unger, Fred; Mariner, Jeffrey C. (International Society for Veterinary Epidemiology and Economics, 2012)
This study was designed to measure the transmissibility of Type A H5N1 highly pathogenic avian influenza (HPAI) in mixed populations of backyard and small-scale commercial chickens in Java. An approach adapted from infection tree reconstruction was used to trace affected chickens and households in neighborhoods (RTs) in which HPAI had been diagnosed by Indonesia’s surveillance system. Of the 41 outbreaks studied, 15 were in RTs participating in a mass vaccination program. The study found that backyard chickens were free range, visiting a mean 4.2 households. Commercial poultry were present within the village in nearly half of the outbreaks, although they were affected in only 7.3%. The distance from the index to the closest unaffected household was significantly greater than that from the index to the closest affected. Mean morbidity was 80.9±28.8%, mortality 77.6±27.7%, and case fatality 97.3±12.3%. There was significant risk for outbreaks to occur in households where Muscovy ducks, non-commercial chickens, broilers and geese were kept, but there was not a significant risk associated with keeping pigeons or ducks (Anatidae family not including Muscovy). Introduction of new birds to a household flock was most frequently documented to have led to the introduction of the disease to an RT, while contact between birds from different household flocks was most frequently documented to have contributed to spread. Transmission between birds within flocks was significantly higher than transmission between flocks, between birds within flocks in vaccinated areas was significantly lower than in unvaccinated areas, and between flocks in vaccinated areas was significantly lower than in unvaccinated areas. Our findings indicate that backyard poultry populations as they occur on Java provide the necessary environment for indefinite HPAI transmission.